2020
DOI: 10.1186/s12896-020-00649-4
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin nanoparticles enable water dispersibility and potentialize the antimicrobial activity of Buriti (Mauritia flexuosa) oil

Abstract: Background Buriti oil presents numerous health benefits, but due to its lipophilic nature and high oxidation, it is impossible to incorporate it into aqueous food matrices. Thus, the present study evaluated whether powder nanoparticles based on porcine gelatin (OPG) and in combination with sodium alginate (OAG) containing buriti oil obtained by O/W emulsification followed by freeze-drying enabled water dispersibility and preserved or increased the antimicrobial activity of the oil. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 65 publications
(80 reference statements)
1
17
0
Order By: Relevance
“…Okada et al [ 48 ] evaluated the pioglitazone’s action, a thiazolidinedione (TZD) in KKAy mice. The results showed that pioglitazone regulated the production of lipoxin B4 (LXB4), a lipid mediator, in adipocytes, decreased Prostaglandin 2, and induced the mRNA expression of IL-10 , IL-13 , and Arg-1 , concluding that this mediator may have an anti-inflammatory effect on adipose tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Okada et al [ 48 ] evaluated the pioglitazone’s action, a thiazolidinedione (TZD) in KKAy mice. The results showed that pioglitazone regulated the production of lipoxin B4 (LXB4), a lipid mediator, in adipocytes, decreased Prostaglandin 2, and induced the mRNA expression of IL-10 , IL-13 , and Arg-1 , concluding that this mediator may have an anti-inflammatory effect on adipose tissue.…”
Section: Resultsmentioning
confidence: 99%
“…The consumption of native fruits in tropical regions has been growing due to their antioxidant, anti-inflammatory, and hypocholesterolemic activity claims [ 14 , 15 , 16 , 17 ]. These effects have been related to their high content of vitamins, carotenoids, and polyphenols [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The oil's oxidation process causes unpleasant tastes, loses nutrients, and produces many toxic compounds (hydroperoxides and aldehydes) that cause mutation, aging, stroke, emphysema, heart disease, and cancer [19]. Another technological obstacle associated with the use of buriti oil in foods is associated with its lipophilic nature, which makes it challenging to apply in products with aqueous matrices, limiting the development of new products [20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, reducing the size to the nanometric scale (< 100 nm) facilitates dispersion of lipophilic substances in an aqueous matrix due to the increase in the contact surface. It can also preserve or enhance the biological properties of bioactive compounds [19][20][21][22]. Thus, nanoencapsulation can increase the antioxidant and antimicrobial potential, among other functionalities, reducing the concentration of the bioactive of interest necessary to achieve the desired effect [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation